2022
DOI: 10.1145/3477399
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling and Analysis of Seljukid Muqarnas in Kayseri

Abstract: As a historical and ornamental building element, muqarnas are widely found among the entrances of madrasas, mosques, and hans in Anatolian Seljuk architecture. In Kayseri (Turkey), muqarnas structures are characterized by symmetrical distribution of patterned geometric layers that presents computational rules for the design and construction of these ornamental structures. The presented research focuses on 12 unique muqarnas structures that are analyzed through a computational methodology combining photogrammet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Dinçer and Yazar [174] compared different case studies for the digital modeling of muqarnas systems in which variations were developed by element-based, tessellation-based, and block-based workflow. More recently, Gokmen et al [175] focused on 12 unique muqarnas structures found in Anatolia that were analyzed through a computational methodology combining photogrammetry, three-dimensional modeling, symmetry, and graph theory. Finally, Agirbas et al [176] investigated the symmetrical proportion of inequality of star edge lengths in muqarnas ground projection plans obtained by 3D laser scanning and examination based on shape grammar.…”
Section: Aesthetic-based; Generation Methods and Variationsmentioning
confidence: 99%
“…Dinçer and Yazar [174] compared different case studies for the digital modeling of muqarnas systems in which variations were developed by element-based, tessellation-based, and block-based workflow. More recently, Gokmen et al [175] focused on 12 unique muqarnas structures found in Anatolia that were analyzed through a computational methodology combining photogrammetry, three-dimensional modeling, symmetry, and graph theory. Finally, Agirbas et al [176] investigated the symmetrical proportion of inequality of star edge lengths in muqarnas ground projection plans obtained by 3D laser scanning and examination based on shape grammar.…”
Section: Aesthetic-based; Generation Methods and Variationsmentioning
confidence: 99%
“…On the other hand, there are many studies on muqarnas compositions in the Iberian Peninsula [43][44][45], Morocco [46], the Mediterranean basin [47][48][49], Persia [50], and elsewhere [51,52] Later examples, also in Palermo, can be found in the Zisa Palace and the Quba Palace [53][54][55].…”
Section: Preliminary Studies On Muqarnasmentioning
confidence: 99%
“…On the other hand, there are many studies on muqarnas compositions in the Iberian Peninsula [43][44][45], Morocco [46], the Mediterranean basin [47][48][49], Persia [50], and elsewhere [51,52]. Among the earliest examples of muqarnas from the West is the wooden ceiling of the Palatine Chapel of the Royal Palace of Ruggero II in Palermo (ca.…”
Section: Preliminary Studies On Muqarnasmentioning
confidence: 99%